Induction of a Senescence-Like Phenotype in Cultured Human Fetal Microglia During HIV-1 Infection. (5th February 2018) - Chen, Natalie C; Partridge, Andrea T; Tuzer, Ferit; Cohen, Justin; Nacarelli, Timothy; Navas-Martín, Sonia; Sell, Christian; Torres, Claudio; Martín-García, Julio
Abstract: HIV-1 causes premature aging in chronically infected patients. Despite effective anti-retroviral therapy, around 50% of patients suffer HIV-associated neurocognitive disorders (HAND), which likely potentiate aging-associated neurocognitive decline. Microglia support productive HIV-1 infection in the brain. Elevated markers of cellular senescence, including p53 and p21, have been detected in brain tissues from patients with HAND, but the potential for microglia senescence during HIV-1 infection has not been investigated. We hypothesized that HIV-1 can induce senescence in microglia. Primary human fetal microglia were exposed to single-round infectious HIV-1 pseudotypes or controls, and examined for markers of senescence. Post-infection, microglia had significantly elevated: senescence-associated β-galactosidase activity, p21 levels, and production of cytokines such as IL-6 and IL-8, potentially indicative of a senescence-associated secretory phenotype. We also found increased detection of p53-binding protein foci in microglia nuclei post-infection. Additionally, we examined mitochondrial reactive oxygen species (ROS) and respiration, and found significantly increased mitochondrial ROS levels and decreased ATP-linked respiration during HIV-1 infection. Supernatant transfer from infected cultures to naïve microglia resulted in elevated p21 and caveolin-1 levels, and IL-8 production. Finally, nucleoside treatment reduced senescence markers induction in microglia. Overall, HIV-1 induces a senescence-like phenotype in human microglia, which could play a role in HAND.